P-628 Do ovarian reserve markers and female age predict the rate of euploid blastocysts in IVF/ICSI cycles?. (30th June 2022) - Marqueta, L; Lawrenz, B; Patel, R; Loja Vitorino, R; Ruiz, F; Bayram, A; Elkhatib, I; Fatemi, H; Melado, L
Abstract: Study question: Are female age and ovarian reserve markers (anti-Mullerian hormone (AMH) and Antral Follicle Count (AFC)), able to predict euploid blastocyst rate in IVF/ICSI cycles? Summary answer: Female age, serum AMH, AFC and the number of mature oocytes collected during IVF/ICSI cycles significantly affect the rate of euploid blastocysts What is known already: The age-associated decline in female reproduction has been clearly demonstrated, due to the reduction of the ovarian reserve and the increased risk of chromosomal abnormality occurring in the oocyte. Lately, it has been debated whether a reduced ovarian reserve, independently of age, could be associated with higher aneuploidy rate in embryos. Ovarian reserve can now be accurately measured by serum AMH levels and AFC, both markers with similar high reliability. Study design, size, duration: This analysis includes data from 10556 blastocysts after preimplantation genetic testing for aneuploidy (PGT-A) with Next Generation Sequencing (NGS). Embryos were obtained from 2564 IVF/ICSI cycles of infertile couples, at ART Fertility Clinics UAE, from November 2016 to December 2020. Participants/materials, setting, methods: 10556 blastocysts with chromosomal information for ploidy were included, mosaic and non-informative embryos were excluded. Trophectoderm biopsy was performed on day 5, 6 or 7 blastocysts. Serum AMH concentrations were measured by Elecsys ® AMH automated assay (Cobas 601 platform, Roche ® ) for all patients in a single laboratory. AFC (sum of small antral follicles in both ovaries) was evaluated with transvaginal 2D-sonography (Voluson E8, GE Healthcare). Ethical approval was obtained from the Research Ethics Committee (REFA023b). Main results and the role of chance: Patients' characteristics are described as mean ± SD (min-max): age: 34.72±6.13(18-50), years of infertility: 3.43±3.43(0-25), AMH: 2.52±2.70ng/mL(0.01-23.00), AFC: 11.57±7.86(0-61), body mass index (BMI): 28.57±4.83Kg/m2(14.34-44.96), Metaphase II (MII) inseminated oocytes: 10.11±6.53(1-50), 2PN embryos 7.32±5.12(1-42), blastocysts 4.12±3.21(1-26). Fertilization rate was 73.31%(±19.30), blastulation rate 61.05%(±25.69) and euploidy rate 39.42%(±35.24). A significant negative Pearson correlation coefficient was found between age and euploidy rate (ρ=-0.5398, p < 0.001). AMH, AFC and total of MII inseminated oocytes showed a significant positive Pearson correlation coefficient with euploid rate (AMH:ρ=0.2076, p < 0.001; AFC: ρ = 0.2578, p < 0.001; MII:ρ=0.2036, p < 0.001). Linear regression analysis was conducted to evaluate the predictability of the variables on euploid rate. As expected, age clearly had a negative impact (Coef=-3.10, Std. Err=0.10, p < 0.0001). A positive effect was observed for AMH (Coef=2.75, Std. Err=0.31, p < 0.0001), AFC (Coef=1.16, Std. Err=0.09, p < 0.0001), number of MII inseminated oocytes (Coef=1.10, Std. Err=0.10, p < 0.0001) and 2PN embryos (Coef=1.43, Std. Err=0.13, p < 0.0001). For patients >35 years old and AMH lower than 1.3 ng/mL, euploid rate was significantly lower compared with the patients >35 years old and AMH equal or higher than 1.3 ng/mL (21.2% vs 25.5%, p = 0.0192). Limitations, reasons for caution: Despite the large number of cycles and embryos included, the retrospective study design is a limitation. Wider implications of the findings: Ovarian reserve is not only a quantitative, but also a qualitative biomarker of oocyte-embryo competence. Cumulative success rates for IVF/ICSI cycles are dependent on the availability of euploid blastocysts. Age and ovarian reserve markers should be combined for adequate counselling. Trial registration number: Not applicable